Psikoanalisis Sigmund Freud dalam Novel Hijab Palsu Karya Kifa Ansu - Mela Khairani; Noni Andriyani (UIR Press, 2023)
The theoretical research is motivated by several things, including the use of hijab on female characters in the novel Fake Hijab by Kifa Ansu based on Sigmund Freud's psychoanalytic study. The problem in this study is how the psychological aspects of female and male characters in the novel Fake Hijab by Kifa Ansu. The data in this study are all the elements of the story in the novel Fake Hijab by Kifa Ansu based on Sigmund Freud's psychoanalytic theory. The method used in this research is descriptive qualitative method and this type of research is library research. The data source for this research is the text of the novel Fake Hijab by Kifa Ansu. The data collection technique in this study was a hermeneutic technique, namely reading, noting, and concluding. The results of the study show that there are id, ego, and superego in the novel Fake Hijab by Kifa Ansu. The results of this study indicate that the most dominant aspect of the superego personality. The id is related to the principle of pleasure which always seeks pleasure in the novel Fake Hijab by Kifa Ansu, which shows that when humans are able to control their ego and lead them to the superego, it will have a good impact on them. Therefore, the personality aspects of the id, ego and superego in humans must be balanced.